Pleiotropic Clostridioides difficile Cyclophilin PpiB Controls Cysteine-Tolerance, Toxin Production, the Central Metabolism and Multiple Stress Responses - Ünal, Can Murat; Karagöz, Mustafa Safa; Berges, Mareike; Priebe, Christina; Borrero de Acuña, José Manuel; Wissing, Josef; Jänsch, Lothar; Jahn, Dieter; Steinert, Michael (Frontiers in Pharmacology, 2019)
ABSTRACT The Gram-positive pathogen Clostridioides difficile is the main bacterial agent of nosocomial antibiotic associated diarrhea. Bacterial peptidyl-prolyl-cis/trans-isomerases (PPIases) are well established modulators of virulence that influence the outcome of human pathologies during infections. Here, we present the first interactomic network of the sole cyclophilin-type PPIase of C. difficile (CdPpiB) and show that it has diverse interaction partners including major enzymes of the amino acid-dependent energy (LdhA, EtfAB, Had, Acd) and the glucose-derived (Fba, GapA, Pfo, Pyk, Pyc) central metabolism. Proteins of the general (UspA), oxidative (Rbr1,2,3, Dsr), alkaline (YloU, YphY) and cold shock (CspB) response were found bound to CdPpiB. The transcriptional (Lrp), translational (InfC, RFF) and folding (GroS, DnaK) control proteins were also found attached. For a crucial enzyme of cysteine metabolism, O-acetylserine sulfhydrylase (CysK), the global transcription regulator Lrp and the flagellar subunit FliC, these interactions were independently confirmed using a bacterial two hybrid system. The active site residues F50, F109 and F110 of CdPpiB were shown to be important for the interaction with the residue P87 of Lrp. CysK activity after heat denaturation was restored by interaction with CdPpiB. In accordance, tolerance towards cell wall stress caused by the exposure to amoxicillin was reduced. In the absence of CdPpiB, C. difficile was more susceptible towards L-cysteine. At the same time, the cysteine-mediated suppression of toxin production ceased resulting in higher cytotoxicity. In summary, the cyclophilin-type PPIase of C. difficile (CdPpiB) coordinates major cellular processes via its interaction with major regulators of transcription, translation, protein folding, stress response and the central metabolism.